2021
DOI: 10.1016/j.gca.2021.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation of calcium-magnesium pyroxenes: Physical-chemical controls and effects of reaction-driven fracturing

Abstract: The weathering of primary silicates, and their carbonation in particular, is key for the geochemical cycling of elements, strongly affecting the C cycle and the long-term regulation of the Earth's climate. The knowledge on the controlling factors and mechanisms of aqueous carbonation of primary silicates is however still far from complete. This precludes a better understanding of their chemical weathering in nature and is a strong handicap to implement effective Carbon Capture and Storage (CCS) strategies. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 105 publications
(180 reference statements)
0
11
0
Order By: Relevance
“…This is because at low temperatures, CDR is much faster than solid-state reactions, as has been demonstrated in numerous hydrothermal mineral phase trans- formations in sulfides, 60,74−82 tellurides, 83,84 phosphates, 85,86 carbonates, 87−91 oxides, 92,93 and silicates. 94,95 Fast hydrothermal transformation of marcasite to pyrite is supported by the observations of some natural deposits. For example, in the giant Jinding (Mesozoic−Cenozoic Lanping Basin, southern China) hydrothermal Zn−Pb deposit (80−190 °C; near-neutral pH), pyrite abundance increased gradually at the expense of marcasite through three stages of mineralization; only pyrite was observed in stage 3, when the highest temperatures were reached.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is because at low temperatures, CDR is much faster than solid-state reactions, as has been demonstrated in numerous hydrothermal mineral phase trans- formations in sulfides, 60,74−82 tellurides, 83,84 phosphates, 85,86 carbonates, 87−91 oxides, 92,93 and silicates. 94,95 Fast hydrothermal transformation of marcasite to pyrite is supported by the observations of some natural deposits. For example, in the giant Jinding (Mesozoic−Cenozoic Lanping Basin, southern China) hydrothermal Zn−Pb deposit (80−190 °C; near-neutral pH), pyrite abundance increased gradually at the expense of marcasite through three stages of mineralization; only pyrite was observed in stage 3, when the highest temperatures were reached.…”
Section: Discussionmentioning
confidence: 85%
“…While the catalytic role of hydrothermal fluids in the marcasite to pyrite transformation requires further detailed studies, it is likely that the rapid transformation is due to CDR mineral replacement reactions rather than solid-state transformation. This is because at low temperatures, CDR is much faster than solid-state reactions, as has been demonstrated in numerous hydrothermal mineral phase transformations in sulfides, , tellurides, , phosphates, , carbonates, oxides, , and silicates. , …”
Section: Discussionmentioning
confidence: 97%
“…The magmatic diopsidite can be exposed over a large area constituting several square kilometres 54 , although the global amount of diopsidite cannot be determined. A few experimental studies have probed the carbonation process of diopside 13 , 14 . The abundant calcite forms during carbonation coupled with serpentinization, as presented here in the study of serpentinized diopsidite (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In nature, large volumes of mafic–ultramafic rocks have been studied to record carbonation processes, especially basaltic rocks, which are rich in calcium, magnesium, iron oxides and highly porous 9 12 showing very promising potential for carbon storage. Neither carbonation nor serpentinization of diopside-rich diopsidite have ever been described in detail for natural samples, although some experimental studies have explored carbonation processes of diopside 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of the primary crystal takes place along fractures since they provide a path for the infiltration of the fluid phase. It has been interpreted that cracks form due to the stress generated by the increase in the molar volume. , Furthermore, it has been stated that the nucleation of crystals of the secondary phase on point and line defects of the primary phase surfaces generates stress-concentrating environments from where fracturing propagates, similarly as that observed during metal corrosion. Surprisingly, despite the significant increase in the molar volume associated to the transformation of calcite into strontianite (+5.6%) and the very large one associated to its transformation into witherite (+24.1%), no cracks are observed in crosscut sections of calcite crystals partially replaced by either strontianite or witherite, even after 2 years interaction with the fluid. Gillet et al (1987) observed that during the pseudomorphic replacement of abiogenic aragonite by calcite, which involves a molar volume change of +8.4%, fracturing only occurred when calcite crystals in the overgrowth reached sizes well over 50 micrometres.…”
Section: Discussionmentioning
confidence: 99%